Applying self-determination theory to understand consumer behavior in e-commerce: An analysis of impulsive buying and its impact on economic wellbeing - Annisa Citra Wahyuni; Yolanda Masnita; Nuraini Chaniago; A. A. Apysheva (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study examines the influence of limited-time deals, perceived ease of use, and hedonic motivation on online impulsive buying behavior, as well as the effect of impulsive buying on compulsive buying within Indonesian e-commerce platforms. Based on self-determination theory, the research examines both the direct and the mediated relationships among the variables. Using purposive sampling, data were collected from 253 Indonesian consumers who actively shop on platforms such as Shopee, Tokopedia, and Lazada. The data were analyzed using Structural Equation Modeling (SEM). The results show that limited-time deals significantly increase both hedonic motivation and online impulsive buying behavior. Hedonic motivation also demonstrates a significant positive effect on impulsive buying and successfully mediates the relationship between limited-time deals and online impulsive buying behavior. In contrast, perceived ease of use does not exhibit a positive effect on impulsive buying. Furthermore, online impulsive buying behavior strongly predicts compulsive buying, suggesting a progression from spontaneous purchases to more repetitive, uncontrolled buying patterns. The novelty of this study lies in integrating promotional scarcity strategies with motivational mechanisms derived from self-determination theory to explain impulsive and compulsive buying tendencies in digital shopping environments. The findings provide theoretical contributions by clarifying the mediating role of hedonic motivation and practical insights for e-commerce marketers. Specifically, the results suggest that urgency-based promotions can enhance emotional engagement and stimulate spontaneous purchases, while ineffective ease-of-use features may not contribute to impulsive behaviors. These insights can help marketers design more effective and responsible promotional strategies.